THE EFFECTIVENESS OF SOCIAL MEDIA IN ENHANCING PUBLIC ENGAGEMENT AND TRUST: A STUDY ON ISLAMIC PUBLIC RELATIONS AT BAZNAS NORTH SUMATRA - Afdal Hafiz Takar; Fauzul Azmi Daulay; Rashin Salsabila; Rara Ardina Khairi (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the effectiveness of social media in enhancing public engagement and trust toward the National Zakat Board (BAZNAS) of North Sumatra, particularly within the context of Islamic public relations. In today's digital era, social media serves as a strategic medium for delivering information rapidly, transparently, and broadly to the public. As a zakat management institution, BAZNAS bears the responsibility of building public trust through effective communication grounded in Islamic values. Through platforms such as Instagram, TikTok, and its official website, BAZNAS North Sumatra utilizes informative, interactive, and persuasive content to encourage public participation and strengthen institutional credibility.This research adopts a qualitative approach using a case study method. Data were collected through in depth interviews, participatory observation, and content analysis of BAZNAS North Sumatra’s social media channels. The findings indicate that the digital communication strategy employed by BAZNAS has been relatively successful in fostering positive relationships with its audience. Public engagement is reflected in the high level of interaction on Instagram and TikTok, while the website functions as an information hub that reinforces transparency.Key factors influencing the effectiveness of BAZNAS’s digital communication include the transparent presentation of information through infographics and fund distribution reports, prompt responsiveness to public inquiries, and active collaboration with religious figures and influencers. These elements have directly contributed to increased public trust in the institution. This study recommends improving content consistency, strengthening collaborative strategies, and optimizing interactive website features as strategic steps for advancing sustainable Islamic public relations through social media.